Inflammatory pathology in depression and suicide: a mechanistic distillation of clinical correlates - Costanza, Alessandra; Amerio, Andrea; Aguglia, Andrea; Magnani, Luca; Parise, Alberto; Nguyen, Khoa D.; Berardelli, Isabella; Pompili, Maurizio; Amore, Mario; Serafini, Gianluca (Frontiers in Immunology, 2024)
The association between inflammation with depression and suicide has prompted many investigations of the potential contributors to inflammatory pathology in these psychiatric illnesses. However, a distillation of diverse clinical findings into an integrated framework of the possible involvement of major physiological processes in the elicitation of pathological inflammation in depression and suicide has not yet been explored. Therefore, this review aims to provide a concise synthesis of notable clinical correlates of inflammatory pathology in subjects with various depressive and suicidal clinical subtypes into a mechanistic framework, which includes aberrant immune activation, deregulated neuroendocrine signaling, and impaired host-microbe interaction. These issues are of significant research interest as their possible interplays might be involved in the development of distinct subtypes of depression and suicide. We conclude the review with discussion of a pathway-focused therapeutic approach to address inflammatory pathology in these psychiatric illnesses within the realm of personalized care for affected patients.